Aspek Lokalitas Tafsir Kitab Tajal-Muslimin Min Kalaami Rabbil Al-Amin Karya K.H Misbah Mustafa - Akbar, Muhammad; Ainiah, Eka Mahabatul; Siregar, Maisarah; Nugraha, Rasyid Tahta (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
It takes more than reading comprehension to become a mufassir of the Qur'an. A mufassir will also talk on political and cultural issues. Key aspects to examine while studying tafsir in Indonesia include the author's social and political conditions, the audience space at the time the tafsir was written, the language utilized, and the aim of authoring the tafsir. The methods used in this study are qualitative. In this investigation, Tafsir K.H. Misbah Mustafa is the focus. This study draws on findings from Tafsir Tajal-Muslimin Min Kalaami Rabbil Al-Amin and other primary and secondary sources, including: Tajal-Muslimin Min Kalaami Rabbil Al-Amin's physical location. A Muslim Is Not Complete Without His Rabbi BBI Al-Alamin is composed of three sections. 1) Places where pegon script is used. 2) Converting the meaning of gandul into pegon script. Second, the ability to converse in Javanese. Localization of meaning. Several traditions are attacked by K.H. Misbah Mustafa. The same as in Surah al-Baqarah (QS) 134. He has a particular interest in the tahlil era and is critical of the qabliyah sunnah community. Those who fast in dhikr are also targets of his criticism. Keywords: Misbah Mustafa, Tafsir Tajal Muslimin, Locality.